The Effectiveness of Using Teaching English for Young Learner (TEYL) Module for Pre-service Teacher Based on Teacher Training Approach - Nirwana Darwis; Uswatun Hasanah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
Teaching English for young learner by the pre-service teacher of PGMI Study Program at IAIN Bone have its challenge. One of the challenges faced by teachers is the use of learning modules that are appropriate and in accordance with the needs of students. This research is focused on the effectiveness of teaching English for Young learner (TEYL) Module based on teacher training approach. The research applied quantitative research by using rubric of students’ achievement in collecting data. The subject in this research is 25 students in PGMI Study Program. In evaluating the students’ achievement, the researchers use semantic differential scales. The result of the research shows that the students score that categorized good; (82.42).It mean that using the TEYL module is satisfying to be implemented in the class. Therefore,It can stated that the module is effective to use in teaching English for Young Learner (TEYL) in PGMI Study Program IAIN Bone.